Analisis Hukum terhadap Kesenjangan Kepastian Hukum dan Keadilan dalam Kasus Pengalihan Hak Paten Konstruksi Sarang Laba Laba di Indonesia - Intan Maharani; Muh Amin Saleh (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study analyzes the gap between legal certainty and justice in patent protection in Indonesia through a case study of the transfer of patent rights for the Spider Nest Construction. The problem formulation includes two things. First, what is the form of distortion of legal certainty in the transfer of patent rights. Second, how is the violation of the inventor's moral and economic rights and the institutional factors that cause it. The method used is normative juridical with a statutory, case, conceptual, and comparative approach. The results of the study indicate that the distortion of legal certainty occurs because the registration of the transfer of rights only uses a Power of Attorney without an authentic deed, which violates Article 11 of the Patent Law. In addition, the unilateral action of the Directorate General of Intellectual Property to freeze and revoke the freezing of patents without a court decision violates Article 132 of the Patent Law. Violation of moral rights is manifested in the form of false attribution in the JALLA patent. Economic rights are ignored through embezzlement of royalties. The peak of injustice is the accusation of plagiarism against the original inventor for his own development invention. Inhibiting factors include institutional weaknesses within the Directorate General of Intellectual Property, excessive judicial intervention, low human resource capacity, regulatory disharmony, and an unsupportive legal culture. Strengthening strategies include institutional reform, revision of the Patent Law, ratification of international conventions, digitalization, international certification, and the establishment of a specialized intellectual property court. In conclusion, without strengthening integrated intellectual property legal policy, the gap between procedural legal certainty and substantive justice will continue to weaken the national innovation ecosystem.